BENTUK TANGGUNG JAWAB KONSTITUSI PEMERINTAH TERHADAP KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA (KPPS) DALAM PEMILU 2019: TRAGEDI DEMOKRASI PEMILU - tajaswari, visi jiwa; Asmorojati, Anom Wahyu (Legal Standing : Jurnal Ilmu Hukum, 2021)
This writing aims to determine the form of Government accountability to KPPS who died in the implementation of the 2019 General Election based on Law No. 7 of 2017 concerning Elections, and aims to determine the form of legal protection for KPPS officers assigned to the 2019 Election based on Law No. 7 of 2017 concerning Elections. The type of research used in the preparation of this paper is a normative legal research method, this research is only aimed at written regulations so that this research is closely related to libraries that require secondary data in the library. The data collection method used in the preparation of this paper is the literature study method, the data analysis carried out in the preparation of this paper is a qualitative descriptive method which aims to reveal events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by presenting what actually happened. The results of this study are a form of government accountability to KPPS officers who died in the 2019 Election in the form of compensation worth 36 million rupiah, this compensation is given to the families of victims who have been left behind. This proposal regarding the nominal compensation money is proposed by the KPU and approved by the Ministry of Finance. The compensation is given directly by the Ministry of Finance to be submitted through the KPU and also BAWASLU as the party with the authority to hand over the compensation to the victim's family. Legal protection for KPPS which is assigned to hold the 2019 Election, namely, is stated in the 1945 Constitution Article 28D paragraph (1) regarding equality before the law to obtain protection without discrimination.